Rekomendari Solusi dan Pembangunan Model Prediksi Keterlambatan di PT. X Menggunakan Decision Tree Regression - Keshia Karina Mulia; Iwan Halim Sahputra (Jurnal Titra, 2021)
For companies engaged in delivery services, punctuality is the main factor that can directly affect customer satisfaction and is one of the main benchmarks for company performance. Therefore, analyzing the root causes of delays needs to be done to provide improvement proposals that can prevent, reduce and overcome the root problems.One of the root causes chosen by the researcher to be studied further is the problem of delays caused by traffic jams. Decision Support System is required to assist companies in making decisions regarding departure time to reduce late deliveries The method that will be used to predict the delay is Decision Tree Regression. The accuracy of the prediction results will be measured based on the value of the Root Square Mean Error. The results show that Decision Tree Regression is still not right for predicting delays, so the truck departure schedule will be pegged based on the travel time or the length of the truck's journey from the depot to the customer's warehouse. The company can also implement other improvement proposals to improve the system in the company, so it can prevent and reduce the impact of delays.